2013
DOI: 10.1002/chp.21201
|View full text |Cite
|
Sign up to set email alerts
|

American Board of Medical Specialties Maintenance of Certification: Theory and Evidence Regarding the Current Framework

Abstract: The American Board of Medical Specialties Maintenance of Certification Program (ABMS MOC) is designed to provide a comprehensive approach to physician lifelong learning, self-assessment, and quality improvement (QI) through its 4-part framework and coverage of the 6 competencies previously adopted by the ABMS and the Accreditation Council for Graduate Medical Education (ACGME). In this article, the theoretical rationale and exemplary empiric data regarding the MOC program and its individual parts are reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 105 publications
3
55
0
Order By: Relevance
“…Quality measurement and reporting are required by most health care payers, including the U.S. Centers for Medicare and Medicaid Services (10). Moreover, participation in QI activities is now a requirement for maintenance of board certification in both medicine and pediatrics (11). We found that despite ACGME requirements, many fellows were not participating in QI, at least as judged by their program directors.…”
Section: Ats Reportsmentioning
confidence: 91%
“…Quality measurement and reporting are required by most health care payers, including the U.S. Centers for Medicare and Medicaid Services (10). Moreover, participation in QI activities is now a requirement for maintenance of board certification in both medicine and pediatrics (11). We found that despite ACGME requirements, many fellows were not participating in QI, at least as judged by their program directors.…”
Section: Ats Reportsmentioning
confidence: 91%
“…A key question is whether evidence exists to support the ability of the current required MOC framework to accurately assess physician competencies (4). Evidence for MOC is discussed in relation to the current requirements of the American Board of Internal Medicine (ABIM), which is responsible for recertifying diplomates in internal medicine and the medical specialties, including nephrology.…”
Section: Moc Should Be Evidence Basedmentioning
confidence: 99%
“…The multiple choice examination has been designed to be psychometrically sound and to reliably test the competency domain of medical knowledge but not to measure performance in a clinical setting. Although evidence exists linking initial certification examination performance with patient care and health outcomes, similar evidence supporting the value of the MOC examination is minimal (4).…”
Section: Moc Should Be Evidence Basedmentioning
confidence: 99%
“…The concern for the quality of medical education mirrors federal and state investment in ensuring practitioner competency in the interest of public health and safety. Such interest can be seen not only in the implementation of outcomes measures for training (ACGME Milestones) and certification (American Board of Medical Specialties [ABMS] through Maintenance of Certification [MOC]) [4] but also in the response to public concerns about physician error (e.g., the Institute of Medicine's duty hour requirements) [5]. The ACGME Program Requirements initially expected programs and institutions to train residents in fatigue awareness and to devise procedures to handle residents who were too tired to function safely.…”
Section: Regulatory Factorsmentioning
confidence: 99%